Implementasi Metode Sima’i dalam Hafalan Al-Qur’an untuk Santri Putri Pondok Pesantren Mafatihussalam Lampung Selatan - Arina Arina; Etika Pujianti; Finy Muslihatuzzahro (Journal on Education, 2023)
This study aims to identify and analyze the implementation of the sima'i method in memorizing the Koran for female students at the Mafatihussalam Islamic boarding school and to identify and analyze the supporting and inhibiting factors in memorizing the Koran for female students at the Mafatihussalam Islamic boarding school, Sidoharjo Jati village. Great South Lampung. This type of research uses field research, this research method uses a qualitative descriptive method. Sources of data using primary and secondary data sources. Data collection techniques with observation, interviews and documentation. Data analysis techniques using data reduction, data presentation and drawing conclusions. The results showed that the method used at the Mafatihussalam Islamic Boarding School was the sima'i method. The application of the STM method is carried out simultaneously in one meeting by means of the teacher guiding and reciting the targeted verses of the Koran, then followed by the students. If the santri understands the reading correctly, it is submitted to the teacher or ustadz and finally the santri repeats the memorization by repeating the previous memorization first before continuing to the new memorization. From the application of the STM method, there were 2 students who had memorized 30 Juz in a period of 18 months and 21 months, which they did not have the slightest bit of memorization before entering the hut. The supporting factor is that memorizing is easy for students who follow the recommendations to study at the Foundation. And the inhibiting factor is for students who go home and do not follow the recommendations for boarding at the Foundation.